About choice of the optimal strategy for technical rearmament - Дёмина, Елена Борисовна; Дёмин, Дмитрий Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The paper proposed methods for selecting the optimal strategy for modernization,the results of their in engineering enterprises implementation